Analysis of Satpol PP’s Communication Management on Horizontal Conflicts in West Java - Awang Darmawan Putra; Kiki Esa Perdana; Rosilawati Hasanah; Ilyas Nafil Rizqullah; Septia Melati Puteri (Jurnal Manajemen, 2026)
Effective communication management is the foundation for reducing and resolving horizontal conflict, which is disagreement between individuals or groups at the same hierarchical level. Horizontal conflict between the Civil Service Police (Satpol PP) and the public, particularly street vendors, remains a recurring issue in West Java, often leading to social tension and public dissatisfaction. This research aims to analyze the communication management of the West Java Provincial Civil Service Police (Satpol PP) in handling horizontal conflicts with the community. Previous studies rarely discussed communication management strategies for dealing with horizontal conflict. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with 10 key informants, participant observation over three months, and document analysis. The research results show that the Civil Service Police (Satpol PP) implement three stages of communication management: planning, execution, and evaluation. During the planning phase, Satpol PP conducts early detection through routine patrols and coordinates with the Police and the Military. The implementation phase is characterized by a persuasive, humanistic, and professional approach, prioritizing dialog and mediation to avoid repressive actions. Finally, the evaluation stage becomes part of continuous learning, where each case serves as material for improving future strategies. The West Java Provincial Satpol PP has implemented structured and effective communication management in addressing horizontal conflicts. However, there is room for improvement, such as enhancing responsiveness to feedback and adopting a more empathetic and holistic approach, including collaborating with local governments to provide economic solutions for affected communities